Organization Communication and Work Environment in Enhancing Work Motivation Among Civil Cervants on District Area During Covid-19 - Isnawijayani Isnawijayani; Dina Mellita; Siti Rahayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to identify organizational and environmental communication on the work motivation of the State Civil Servant (CS) at the district level during the covid-19 pandemic. The existence of a social restriction policy in activities that was also experienced by CS organizational communication and work environment have an influence on employee motivation. The results showed that during the Covid-19 pandemic the level of CS motivation was low. Through indicators of Basic needs, security needs, social needs, esteem needs and self-actualization, it is known that all indicators in the motivational variable have low values and only indicators of security needs have sufficient values. From the results of regression analysis, it is known that organizational communication and the work environment have an influence on motivation, where good organizational communication can be seen from the effectiveness and openness of information and the relationship between leaders and their subordinates which includes trust, joint decision making, honesty, openness in communication to others. up and down and attention to high-performance goals. Due to a good work environment, it will have an impact on increasing employee motivation to work together to achieve better office goals.